Comparing Branched versus Straight-chained Monoamide Extractants for Actinide Recovery. Issue 1 (2nd January 2018) - McCann, Kevin; Drader, Jessica A.; Braley, Jenifer C.
Abstract : Separations of used nuclear fuel at the engineered scale have generally been completed using the Plutonium Uranium Redox Extraction (PUREX) process. The PUREX process uses tributyl phosphate (TBP) as an extractant to recover uranium and plutonium. While the TBP extractant has proven effective at recovering U and Pu at the engineered scale, TBP is potentially vulnerable to third phase formation and TBP degradation products (monobutyl and dibutyl phosphoric acids) which can complicate recovery of extracted metals from the organic phase. An alternative class of extractants, monoamides, has been considered for applications in thorium and uranium fuel cycles. When compared to TBP, monoamides tend to have higher separation factors for U or Pu from fission products, structural materials, and Th. This review summarizes the literature that explores actinide separations using monoamides by assessing the physiochemical properties between a broader library of branched and straight-chain monoamides than considered in previous reviews. An emphasis is placed on fine-tuning the selectivity of branched monoamides.